Journalism : a beginner's guide - Niblock, Sarah ([S.l.] : Oneworld Publications, 2010)
Journalism today is moving faster than ever before. With web 2.0, blogging, huge media conglomerates, 24-hours news networks, and tight legal frameworks, what is the purpose of journalism in the digital age? With priorities shifting, do journalists still strive for truth or are they solely concerned with "infotainment" -- driven by sales and ratings? This captivating guide explains the history of journalism, its everyday workings, and the ethical dilemmas that modern journalists face. Sarah Niblock is Head of Journalism at Brunel University, UK. As a journalist, she has written for the Independent, the Guardian, the Telegraph, and Cosmopolitan Magazine.
Keywords: Journalism